An Improve Service Quality of Mobile Banking using Deep Learning Method for Customer Satisfaction - Abed N.K.; Shahzad A.; Mohammedali A. (American Institute of Physics Inc., 2024)
The development of the banking sector has become fast thanks to modern technologies, which have affected many aspects of life. The quality of service in mobile banking has witnessed rapid development due to its information-rich nature and its need for speed and accuracy in processing information. Deep Learning is considered one of the emerging technologies recently, so it was adopted in the development of the banking sector, as well as the lack of previous research that focused on its applications in banks. Proposed study considered two banks in Iraq (Al-Rafidain and Al-Rashid bank). In this context, the hypotheses that focus on the statistical aspect and the construction of a deep neural network were relied upon in order to obtain accurate and fast information at the same time. However, the results were good and could be developed in the future to include more variables and more hypotheses, in addition to accommodating a larger questionnaire with the same accuracy. 2023 American Institute of Physics Inc.. All rights reserved.